2019
DOI: 10.21608/ejfs.2019.12089.1005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of purslane (Portulaca oleracea L.) extract as antioxidant and antimicrobial agent on overall quality and shelf life of Greek-style yoghurt

Abstract: T HIS study investigated the effect of purslane (Portulaca oleracea L.) leaves extract onGreek-style yogurt. Purslane extract showed higher antioxidant values and antimicrobial activity against Escherichia coli ATCC25922; Salmonella typhimurium ATCC14028. The fortified of Greek-style yoghurt with lyophilized purslane extract 2.2g/L (S1) and 4.4g/L (S2) significantly increased the antioxidant capacity. Greek-style yoghurt made with 4.4g/L lyophilized purslane extract received the highest antioxidant capacity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Agawane et al [55] found that the methanolic leaves extract of Mentha arvensis L. showed ability to scavenge DPPH free radical which was found to be 78% at concentration 1000mg/mL. The effect of antioxidative components on inhibition of DPPH radical is considered to be due to their ability of hydrogen-donating [64].…”
Section: Discussionmentioning
confidence: 99%
“…Agawane et al [55] found that the methanolic leaves extract of Mentha arvensis L. showed ability to scavenge DPPH free radical which was found to be 78% at concentration 1000mg/mL. The effect of antioxidative components on inhibition of DPPH radical is considered to be due to their ability of hydrogen-donating [64].…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation was reported in the ferric reducing antioxidant power (FRAP) assay. For example, El-Sayed et al [17] described a reduced antioxidant activity of purslane-fortified Greek-Style yogurt during cold storage due to milk protein-polyphenol interactions. Another major limitation of the DPPH assay is the overlapped spectra of compounds that absorb in the same wavelength range as DPPH.…”
Section: Spectrophotometric Methodologiesmentioning
confidence: 99%
“…Despite this, Zhang et al [59] in their study indicated that a saturated solution of lead acetate and 5% potassium oxalate is more suitable for protein removal from fortified milk than isoelectric precipitation. Acid precipitation combined with alkaline treatment was used for purslane-fortified Greek-style yogurt by El-Sayed et al [17]. For this, yogurt samples were homogenized with distilled water, and the pH was readjusted by the addition of 2.5 mL HCl to 4.…”
Section: Fortified Foodsmentioning
confidence: 99%
“…A number of reports exist in the literature on the ethnomedicinal and pharmacological profiles of purslane [4][5][6][7]. Purslane extracts demonstrate various pharmacological activities, such as antioxidant [2,8,9], anti-inflammatory [10][11][12], neuroprotective [13][14][15], antimicrobial [16,17], antidiabetic [18][19][20], antiulcerogenic [21], and anticancer [19,22,23].…”
Section: Introductionmentioning
confidence: 99%